2012
DOI: 10.1111/j.1537-2995.2012.03737.x
|View full text |Cite
|
Sign up to set email alerts
|

A Web‐based approach to blood donor preparation

Abstract: Web-based donor preparation materials may provide a cost-effective way to enhance donation intentions and encourage donation behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 29 publications
4
49
0
1
Order By: Relevance
“…Katz et al [31] have demonstrated that computerized donor screening increases and improves the accuracy and efficiency of the BD process. Another research work [32] has demonstrated that web-based educational material can reduce anxiety and enhance BD attitudes. BD apps can be an efficient means to motivate users to give blood or to help them find eligible donors.…”
Section: Introductionmentioning
confidence: 98%
“…Katz et al [31] have demonstrated that computerized donor screening increases and improves the accuracy and efficiency of the BD process. Another research work [32] has demonstrated that web-based educational material can reduce anxiety and enhance BD attitudes. BD apps can be an efficient means to motivate users to give blood or to help them find eligible donors.…”
Section: Introductionmentioning
confidence: 98%
“…Researchers also improved communications to donors through an enhanced donor recruitment brochure [63,67], use of a video [68], or through a better website [69]. The goals for each of these improvements were to reduce fear, decrease vasovagal reaction rates, and increase blood donor retention.…”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%
“…There was no synergy from doing both. An improved web-based approach was evaluated in 673 college students, 60% of whom were non-donors [69]. In non-donors, the authors' website produced greater changes in donor attitude, confidence, and intention than the standard website and the control website, and in donors, the authors' website produced greater changes in donor confidence than the standard website and control website.…”
Section: Reducing Vasovagal Reactions and Increasing Donor Retentionmentioning
confidence: 99%
“…Participants assigned to the competence group are instructed to review a donor coping website [36] that combines text, videos, and interactive features to directly address common donor fears and to offer advice on empirically-validated strategies to reduce fear, pain, and syncopal reactions.…”
Section: Design and Methodsmentioning
confidence: 99%
“…For instance, we have demonstrated that self-efficacy or feelings of competence as a blood donor is enhanced through exposure to coping materials that address common donor fears and concerns [17, 3639]. We have also demonstrated that a brief telephone interview based on motivational interviewing principles, which encourages donors to reflect on their unique motivations for giving, has a positive effect on internal motivation [40] and subsequent donation behavior [41].…”
Section: Introductionmentioning
confidence: 99%